Pengendalian Alih Fungsi Lahan Sawah sebagai Upaya Pemenuhan Ruang Terbuka Hijau Kota (RTHK) di Kota Denpasar - Wiraguna, I Gusti Agung Adi; Sueca, Ngakan Putu; Adhika, I Made (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 6 No 1 (2019): April 2019, 2019)
An escalating need for space in a growing city has placed urban agricultural land a target for conversion. This is often done to accommodate the need for housing and commercial development. Many cities in Asia agricultural land comes in the form of rice paddy field and is treated as the main component of urban open space. In this position, the paddy field possesses important environmental, aesthetical, social, and economical values. Realizing this conditin, Local Government for Denpasar for instance, requires 30% of its total area dedicated for urban open space. But a statistical data for this city shows a average decrease of 31.86% of farming land annually. A record for year 2010 demonstrates 2.632 hectare of farmed land available accross the city. This figure droped into 2.409 hectare in 2017. This study aims to determine fundamental factors determining the conversion of agricultural land in Denpasar. It is conducted using a mixed of qualitative and quantitative method. The study reveals the important roles held by various parties involved including government, community, private sector and social institutions, in directing the conversion of agricultural land. This involves a three stages decision making process: planning, organization, and incentive provision. Planning stage is excecuted by stipulating a spatial planning that protects the sustainability of the agricultural zone. Management method is done by developing a Subak Lestari Zone. On top of these two stages, owners of agriclutural lands will also be given incentives in the forms of subsidized fertilizers to ease the cost of farming activities. The proposed methods are to be excecuted based on community participation concept. Keywords: spatial conversion, urban open space, land use control   Abstrak Perkembangan suatu kota memberikan implikasi pada tingginya pemanfaatan ruang kota. Kebutuhan lahan yang meningkat berdampak terhadap munculnnya alih fungsi lahan terutama lahan sawah. Luas lahan sawah yang terus menurun berpengaruh terhadap proses penataan ruang kota. Lahan sawah merupakan salah satu bagian ruang terbuka hijau skala kota. Proporsi ruang terbuka hijau minimum adalah 30% dari luas wilayah kota. Luas lahan sawah di Kota Denpasar mengalami penurunan rata-rata sebesar 31,86 Ha setiap tahunnya. Luas lahan sawah tahun 2010 yaitu 2.632 Ha mengalami penyusutan menjadi 2.409 Ha di tahun 2017. Penelitian ini bertujuan untuk mengetahui upaya pengendalian alih fungsi lahan sawah di Kota Denpasar. Penelitian ini mengunakan metode penelitian yang menggabungkan antara metode kualitatif dan kuantitatif. Penelitian ini menyimpulkan pentingnya eksistensi pemerintah, masyarakat, sektor swasta dan lembaga sosial melakukan intervensi terhadap faktor-faktor penyebab terjadinya alih fungsi lahan sawah. Pengambilan kebijakan dapat dilakukan melalui tiga pendekatan yaitu peraturan, pengelolaan dan pemberian insentif. Pendekatan melalui peraturan secara umum diterapkan pemerintah melalui penetapan rencana tata ruang wilayah. Pendekatan melalui pengelolaan dilakukan dengan pembentukan kawasan subak lestari sebagai bagian dari lahan pertanian pangan berkelanjutan. Pendekatan melalui pemberian insentif dilakukan dengan salah satunya melalui pemberian subsisi pupuk kepada para petani. Bentuk pengendalian lainnya dilakukan dengan pendekatan yang berbasis partisipasi masyarakat.   Kata kunci: alih fungsi lahan sawah, pengendalian, ruang terbuka hijau kota